Valores de hemoglobina y hematocrito en relación con la edad, sexo e índice de masa corporal, en personas mayores de 15 años del mercado ex Mayorista – pasaje Albarracín, de la ciudad de Trujillo, marzo 2018 - Pérez Carrasco, Mary Lisbeth (2019)
The objective of this work was to determine the levels of hemoglobin (Hb) and hematocrit (HCT) in relation to age, sex and body mass index, in people older than 15 years of the Ex Mayorista - Pasaje Albarracín market, in the city of Trujillo, march 2018. The sample is a total of 56 people, of which 26 were men and 30 were women. Anthropometric measurements of height (m) and weight (kg) were made to determine the BMI, and the method used was cyanometahemoglobin and microhematocrit. Regarding the results obtained, the average values were hemoglobin 16.87%; hematocrit 44%; BMI 32.85% and age 40.50%. In hemoglobin levels 8.9% of the attendees had high values, 60.7% normal values and 30.4% low values, and in hematocrit levels 7.2% high values, 85.7% normal values and 7.2% low values. With the results obtained it is concluded that there is no relationship between hemoglobin and hematocrit levels with respect to age, sex and BMI